Alkene Synthesis by Photo‐Wolff‐Kischner Reaction of Sulfur Ylides and N‐Tosylhydrazones. Issue 57 (16th September 2021) - Gao, Pan‐Pan; Yan, Dong‐Mei; Bi, Ming‐Hang; Jiang, Min; Xiao, Wen‐Jing; Chen, Jia‐Rong
Abstract: A visible‐light‐driven and room temperature photo‐Wolff‐Kischner reaction of sulfur ylides and N‐tosylhydrazones has been developed for the first time to provide modular access to alkene synthesis. The high functional group tolerance and broad substrate scope were demonstrated by more than 60 examples. Both E‐ and Z‐olefinic stereochemistry in the products could be controlled with excellent stereoselectivity. A series of mechanistic studies support that the reaction should proceed through a radical‐carbanion crossover pathway, specifically involving addition of photo‐generated sulfur ylide radical cations to N‐tosylhydrazones to form carbanions and subsequent Wolff‐Kischner process. Abstract : A visible‐light‐driven and room temperature photo‐Wolff–Kischner reaction of sulfur ylides and N ‐tosylhydrazones has been developed for the first time to provide modular access to alkene synthesis. The high functional group tolerance and broad substrate scope were demonstrated by more than 60 examples. Both E ‐ and Z ‐olefinic stereochemistry in the products could be controlled with excellent stereoselectivity. A series of mechanistic studies support that the reaction should proceed through a radical‐carbanion crossover pathway. PC=photoredox catalysis. SET=single‐electron transfer.